2020
DOI: 10.3344/kjp.2020.33.2.176
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atropine in preventing catheter-related pain and discomfort in patients undergoing transurethral resection due to bladder tumor; prospective randomized, controlled study

Abstract: Background: Catheter-related bladder discomfort (CRBD) has been observed in many patients undergoing a urethral catheterization. CRBD may be so severe that the patients require additional analgesics. Muscarinic receptors are involved in the mechanism of CRBD. The aim of this study is to determine the effects of the antimuscarinic properties of atropine, which is frequently used in current practice on CRBD, by comparing it with sugammadex which has no antimuscarinic effects. Methods: Sixty patients selected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Recently, Şahiner et al [1] reported a novel study demonstrating the positive effect of intraoperative atropine in the prevention of postoperative catheter-related bladder discomfort (CRBD) following transurethral resection of bladder tumor (TURBT). The aim of this study was to determine the anticholinergic effect of atropine on suppression of bladder contraction that is known to be related to CRBD.…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Şahiner et al [1] reported a novel study demonstrating the positive effect of intraoperative atropine in the prevention of postoperative catheter-related bladder discomfort (CRBD) following transurethral resection of bladder tumor (TURBT). The aim of this study was to determine the anticholinergic effect of atropine on suppression of bladder contraction that is known to be related to CRBD.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Atropine is a cheap and easy-to-use drug with a long history of safe usage. According to Şahiner et al [1], atropine could be an attractive treatment option to treat CRBD without any significant adverse events. The previously used anticholinergics such as butylscopolamine oxybutynin, solifenacin, tolterodine, fesoterodine, imidafenacin, and trospium chloride showed limited effectiveness but caused prominent side effects such as dry mouth and constipation.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Currently, the use of atropine as premedication has been abandoned due to its effects on the central nervous system. In our study, atropine was also intraoperatively administered, and no patient received it outside the operating room [ 1 ]. Thus, we did not observe any side effects.…”
mentioning
confidence: 99%
“…Thus, we did not observe any side effects. As we stated in the materials and methods section, all participating patients were examined preoperatively, and their clinical cardiac statuses were evaluated, and the patients with previously known or symptomatic heart failure and arrhythmia were excluded [ 1 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation